Investigating antimicrobial resistance genes in probiotic products for companion animals - Kerek, Adam; Szabó, Emese; Szabó, Ábel; Papp, Márton; Bányai, Krisztián; Kardos, Gábor; Kaszab, Eszter; Bali, Krisztina; Jerzsele, Ákos (Frontiers in Veterinary Science, 2024)
IntroductionOne of the greatest challenges of our time is antimicrobial resistance, which could become the leading cause of death globally within a few decades. In the context of One Health, it is in the common interest to mitigate the global spread of antimicrobial resistance by seeking alternative solutions, alongside appropriate drug selection and responsible use. Probiotics offer a potential avenue to reduce antibiotic usage; however, there is a scarcity of research that examines commercial products in terms of carrying antimicrobial resistance genes (ARGs) involved in resistance development through microbial vectors.MethodsOur study investigated 10 commercially available probiotic products for cats and dogs. Initially, we conducted phenotypic testing through determination of minimum inhibitory concentration (MIC) for antibiotics important in animal and public health. Subsequently, we performed next-generation sequencing (NGS) of the products to elucidate the genetic background behind the decrease in phenotypic sensitivity.ResultsIn total, 19 types of ARGs were identified, with 57.9% being found on plasmids, and in two cases, carriage as mobile genetic elements were found. One of the genes identified was the APH(3′)-Ia gene, capable of inactivating aminoglycoside antibiotics through phosphotransferase enzyme production regulation, while the other was the tetS gene, capable of conferring reduced sensitivity to tetracycline antibiotics through target protection.DiscussionOur findings underscore the importance of approaching antimicrobial resistance investigations from a broader perspective. We suggest that further studies in this area are justified and raise questions regarding the need to extend legally required studies on probiotic products from their use in economic livestock to their use in companion animals.